Cyberpsychology as Everyday Digital Experience across the Lifespan - Harley, Dave (Palgrave Macmillan UK, 2018)
Digital technologies are deeply embedded in everyday life with opportunities for information access and perpetual social contact now mediating most of our activities and relationships. This book expands the lens of Cyberpsychology to consider how digital experiences play out across the various stages of people's lives. Most psychological research has focused on whether human-technology interactions are a 'good' or a 'bad' thing for humanity. This book offers a distinctive approach to the emergent area of Cyberpsychology, moving beyond these binary dilemmas and considering how popular technologies have come to frame human experience and relationships. In particular the authors explore the role of significant life stages in defining the evolving purpose of digital technologies. They discuss how people's symbiotic relationship with digital technologies has started to redefine our childhoods, how we experience ourselves, how we make friends, our experience of being alone, how we have sex and form romantic relationships, our capacity for being antisocial as well as the experience of growing older and dying. This interdisciplinary book will be of great interest to scholars and practitioners across psychology, digital technology and media studies as well as anyone interested in how technology influences our behaviour.